2007
DOI: 10.1074/jbc.m608830200
|View full text |Cite
|
Sign up to set email alerts
|

Tissue-specific Changes in the Hydroxylysine Content and Cross-links of Collagens and Alterations in Fibril Morphology in Lysyl Hydroxylase 1 Knock-out Mice

Abstract: We have generated mice with targeted inactivation of the Plod1 gene for lysyl hydroxylase 1 (LH1). Its human mutations cause Ehlers-Danlos syndrome VIA (EDS VIA) characterized by muscular hypotonia, joint laxity, and kyphoscoliosis. The Plod1 ؊/؊ mice are flaccid and have gait abnormalities. About 15% of them died because of aortic rupture and smooth muscle cells in non-ruptured Plod1 ؊/؊ aortas showed degenerative changes. Collagen fibrils in the Plod1 ؊/؊ aorta and skin had an abnormal morphology. The LH act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
77
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(89 citation statements)
references
References 41 publications
10
77
0
Order By: Relevance
“…In addition, the levels of free and total Hyl residues in the purified type I collagen were essentially unchanged among the Sh clones and controls, suggesting that the LH activity of LH3, if any, is minimal for bone type I collagen. In the past years, several groups have tried to determine the sequence or collagen type specificity for the activities of LH isoforms (28,29,(63)(64)(65)(66)(67)(68)(69)(70). The results from these studies indicated that there are no strict collagen types or sequence requirements for the individual LH isoforms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the levels of free and total Hyl residues in the purified type I collagen were essentially unchanged among the Sh clones and controls, suggesting that the LH activity of LH3, if any, is minimal for bone type I collagen. In the past years, several groups have tried to determine the sequence or collagen type specificity for the activities of LH isoforms (28,29,(63)(64)(65)(66)(67)(68)(69)(70). The results from these studies indicated that there are no strict collagen types or sequence requirements for the individual LH isoforms.…”
Section: Discussionmentioning
confidence: 99%
“…As for LH3, its contribution to Lys hydroxylation in the helical region of fibrillar collagen is still unclear (28,29,65). When the function of one isoform is impaired, compensatory mechanisms from the other two isoforms may occur and may depend largely on the tissue-specific expression of each isoform (70).…”
Section: Discussionmentioning
confidence: 99%
“…Of these genes, only Mthfr has been suggested as a mediator of renal damage, largely in response to homocysteinemediated oxidative stress in the kidney (Yi and Li 2008). Plod1 is a lysyl hydroxylase that mediates collagen cross-linking, and Plod1 knockout mice are prone to aortic aneurism (Takaluoma et al 2007); however, Plod1 has not yet been associated with renal phenotypes. This is also the first report of a protective effect on proteinuria by Agtrap, a mediator of the renin-angiotensin system (Oppermann et al 2010).…”
Section: Renal Phenotypesmentioning
confidence: 99%
“…The formation of Hyp is essential to stabilize the collagen triple helix and confer its thermal stability at body temperature (Shoulders and Raines 2009). Lysyl hydroxylation is involved in the formation of covalent intra-and inter-molecular crosslinks, contributing to condensation and fibril formation (Takaluoma et al 2007). Hyl also serves as acceptor for the attachment of collagenspecific glycans (Schegg et al 2009).…”
Section: Introductionmentioning
confidence: 99%